ACAULIS5 Is Required for Cytokinin Accumulation and Function During Secondary Growth of Populus Trees - Milhinhos, Ana; Bollhöner, Benjamin; Blazquez, Miguel A.; Novák, Ondřej; Miguel, Célia M.; Tuominen, Hannele (Frontiers in Plant Science, 2020)
In the primary root and young hypocotyl of Arabidopsis, ACAULIS5 promotes translation of SUPPRESSOR OF ACAULIS51 (SAC51) and thereby inhibits cytokinin biosynthesis and vascular cell division. In this study, the relationships between ACAULIS5, SAC51 and cytokinin biosynthesis were investigated during secondary growth of Populus stems. Overexpression of ACAULIS5 from the constitutive 35S promoter in hybrid aspen (Populus tremula × Populus tremuloides) trees suppressed the expression level of ACAULIS5, which resulted in low levels of the physiologically active cytokinin bases as well as their direct riboside precursors in the transgenic lines. Low ACAULIS5 expression and low cytokinin levels of the transgenic trees coincided with low cambial activity of the stem. ACAULIS5 therefore, contrary to its function in young seedlings in Arabidopsis, stimulates cytokinin accumulation and cambial activity during secondary growth of the stem. This function is not derived from maturing secondary xylem tissues as transgenic suppression of ACAULIS5 levels in these tissues did not influence secondary growth. Interestingly, evidence was obtained for increased activity of the anticlinal division of the cambial initials under conditions of low ACAULIS5 expression and low cytokinin accumulation. We propose that ACAULIS5 integrates auxin and cytokinin signalling to promote extensive secondary growth of tree stems.